Transapical Implantation of the SAPIEN 3 Valve. Issue 5 (21st July 2013) - Ribeiro, Henrique B.; Doyle, Daniel; Nombela‐Franco, Luis; Urena, Marina; Allende, Ricardo; De Larochellière, Robert; Rodés‐Cabau, Josep; Dumont, Eric
Abstract We report two cases of high‐risk aortic stenosis treated with the SAPIEN 3 valve. This is the first procedure performed with this type of valve through the transapical approach. This new balloon‐expandable valve incorporates a lower profile cobalt‐chromium stent and an additional outer skirt to enhance paravalvular sealing. The procedure was performed without complications and no paravalvular leak was detected in control echocardiogram at follow‐up. doi: 10.1111/jocs.12189 (J Card Surg 2013;28:506–509)